2021
DOI: 10.3390/toxics9010016
|View full text |Cite
|
Sign up to set email alerts
|

Acute Changes in Thyroid Hormone Levels among Thai Pesticide Sprayers

Abstract: The objective of this study was to investigate the relationship of acute pesticide exposures and acute changes in thyroid hormones among Thai farmers. We recruited 78 farmers, who were scheduled to spray insecticides (chlorpyrifos and/or cypermethrin) or herbicides (paraquat and/or glyphosate). On the day before spraying, farmers collected their first morning void urine and went for blood collection. On the spray day, urine samples were collected at end of the spraying event and they were interviewed with ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 64 publications
1
12
2
Order By: Relevance
“…36 We found a higher risk of thyroid disorders among females and unskilled laborers. Previous studies in Thailand found elevated thyroid hormones among pesticide using farmers compared to organic farmers, 19,20 but our study did not find an elevated risk among agricultural workers. However, the higher prevalence of thyroid disorders among females is consistent with previous studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…36 We found a higher risk of thyroid disorders among females and unskilled laborers. Previous studies in Thailand found elevated thyroid hormones among pesticide using farmers compared to organic farmers, 19,20 but our study did not find an elevated risk among agricultural workers. However, the higher prevalence of thyroid disorders among females is consistent with previous studies.…”
Section: Discussioncontrasting
confidence: 99%
“…18 Additionally, recent studies in Thailand reported dysregulation of thyroid hormone levels among agricultural workers exposed to pesticides. 19,20 Increasing trends in cardiovascular diseases, hypertension, stroke, and diabetes mellitus have created an economic burden in Thailand. 21 In 2009, the economic cost of NCDs was approximately 6617 million USD due to premature deaths and loss of productivity among the workforce.…”
Section: Introductionmentioning
confidence: 99%
“…In that study, we found that exposure to NEOs is related to alterations of red blood cell indices in male farmworkers (a separate manuscript is being prepared). Furthermore, we did not observe any association between DAP concentrations and hematological parameters; however, previous studies reported associations between DAP metabolites and hormones [ 15 , 32 , 33 ]. Although data are available about the relationship between OP exposure and reproductive health and steroid hormones, little has been reported about the association between NEO exposure and human health.…”
Section: Introductioncontrasting
confidence: 92%
“…The most used insecticides in Thailand are the organophosphates and synthetic pyrethroids [4]. Conventional farmers sometimes mix and spray several pesticides together to save time and the cost of spraying, if sprayers are hired [5]. There were 805 pesticide poisoning cases from organophosphate and carbamate pesticides and 58 deaths reported for the period of October 2018 to June 2019 in Thailand [6].…”
Section: Introductionmentioning
confidence: 99%